Waterproof Mechanically Robust Multifunctional Conformal Sensors for Underwater Interactive Human–Machine Interfaces. (1st July 2021) - Duan, Shengshun; Wang, Binghao; Lin, Yucheng; Li, Yinghui; Zhu, Di; Wu, Jun; Xia, Jun; Lei, Wei; Wang, Baoping
Abstract : Wearable sensors with water resistance and mechanical durability are of great value in dealing with long‐term movement and remote control in harsh environments. However, achieving high sensitivity with long‐term stability and real‐time remote control in a watery environment is still a challenge. Herein, the waterproof wearable sensors with good mechanical robustness composed of laser‐induced graphene and in situ‐coated protective silicone layers are reported. By being integrated with high‐capacitance ion‐gel dielectrics, the conformal sensors can detect multiple stimuli, including strain, temperature, and pressure. The long‐term water resistance of strain sensors is evaluated by continuously monitoring the resistance in underwater, sweat, and saline environment for up to 5.5 h. Underwater wireless remote control of a robotic hand is further demonstrated by mounting five sensor arrays. Moreover, different finger gestures are well recognized, making these sensor devices promising candidates for versatile waterproof wearable electronics and robotics technology. Abstract : All‐weather, long‐lasting electronic systems are of value in practical applications. Herein, a multifunctional e‐skin based on laser‐induced graphene possessing both waterproofness and robustness is reported. Then, a wearable hybrid remote‐control system for underwater gesture recognition and control of robots is demonstrated.